Representasi bentuk mimikri sebagai gejala poskolonial dalam kumpulan puisi judul Nyanyian Akar Rumput karya Wiji Thukul - Juidah, Imas; Pratiwi , Veronika Unun (Universitas Mulawarman, 2025)
This study aims to describe the representation of mimicry as a postcolonial symptom in the poetry collection Nyanyian Akar Rumput by Wiji Thukul. This research method is descriptive qualitative. The subject of this study is the poetry collection Nyanyian Akar Rumput by Wiji Thukul. The data collection process was carried out by reading and taking notes. Repeated readings were carried out to identify the main ideas or contents contained in the poems that describe mimicry and resistance in postcolonial studies. The results of this study can be summarized as follows. The form of mimicry is reflected in the characteristics of colonialism such as oppression, slavery, arbitrary behavior, making things difficult and deceitful which are applied to maintain the regime’s power. Meanwhile, forms of resistance include open resistance, covert resistance, and negotiation resistance, but the most commonly found is invisible (covert) resistance, namely a form of defense based on ideology, resistance that is able to protect oneself from the threat of a more intense process of exclusion, covert resistance often requires a long and continuous process.